PENGARUH FAKTOR PRIBADI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Wa Ode Zusnita Muizu; Aji Komarudin (PEKBIS, 2018)
The organization is a collection of coordinated individuals in a structure to realizeorganizational goals. Organizational performance can be realized, if all elementswithin the organization are well coordinated and integrated, according to theirfunction and role. One of the determinants of the achievement of organizational workis the realization of employee performance within the organization. Elements thatsupport employee performance improvement in this study are personal factors andjob satisfaction. Pre-survey results show that employee attitudes are still notupholding trust and commitment in performing tasks, the number of public attentionto the ability of employees who are less responsive, and the number of employeesabsent. This study aims to find out (i) to know and analyze: (i) description ofpersonal factors, job satisfaction, and employee performance, Regency / City WestJava Provincial Offices, (ii) personal factors influence and job satisfaction onemployee performance dnas -department at the District Level / City of West JavaProvince, either partially or simultaneously. The research method used is descriptivesurvey and explanatory survey. Hypothesis in this research is tested by usingStructural Equation Model, while for data processing using LISREL 8.72 program.The results of the first hypothesis testing showed that personal factors andemployee satisfaction affect partially and simultaneously on employee performance.Thus, the better the condition of personal factors of employees, employee jobsatisfaction is also increasing, it will be more optimal achievement of performanceemployees of the Office of West Java Province.